2021
DOI: 10.17305/bjbms.2020.5617
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a ferroptosis-related lncRNAs prognosis signature in colon cancer

Abstract: Ferroptosis is a form of iron-dependent programmed cell death. Regulate ferroptosis in tumor cells is a novel treatment modality. The present study aimed to investigate ferroptosis-related long non-coding RNAs (lncRNAs) and construct a prognostic model for colon adenocarcinoma (COAD). RNA- sequencing data and ferroptosis-related genes were obtained from The Cancer Genome Atlas database and FerrDb database. COAD patients were randomly assigned to training- and validation groups. The Least Absolute Shrinkage and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 34 publications
2
50
0
Order By: Relevance
“…The lack of reliable markers for early tumor diagnosis is still one of the key factors in the dismal prognosis of individuals with advanced STAD. Recent ndings have revealed that ferroptosis-related lncRNAs can act as prognostic targets in diverse cancers (13,14). Thus, we further con rmed the possible predictive value of ferroptosis-related lncRNAs in individuals with STAD.…”
Section: Prognostic Value Of Ferroptosis-related Lncrnas In Stadsupporting
confidence: 58%
See 1 more Smart Citation
“…The lack of reliable markers for early tumor diagnosis is still one of the key factors in the dismal prognosis of individuals with advanced STAD. Recent ndings have revealed that ferroptosis-related lncRNAs can act as prognostic targets in diverse cancers (13,14). Thus, we further con rmed the possible predictive value of ferroptosis-related lncRNAs in individuals with STAD.…”
Section: Prognostic Value Of Ferroptosis-related Lncrnas In Stadsupporting
confidence: 58%
“…The enrichment analyses indicated that ferroptosis-related lncRNAs are closely related to iron metabolism and could mediate some pivotal signaling pathways in tumorigenesis of STAD. (13,14). Thus, we further con rmed the possible predictive value of ferroptosis-related lncRNAs in individuals with STAD.…”
Section: Patient Characteristicssupporting
confidence: 52%
“… 39 Ferroptosis has been investigated in a variety of cancers. For example, an LncRNA prognosis model, which was related to ferroptosis, was developed in colon cancer; 40 The genes related to ferroptosis were potentially prognostic molecular markers for patients with colorectal cancer; 41 Moreover, ferroptotic damage promotes tumorigenesis in pancreatic cancer patients; 42 A model of liver cancer patients was constructed, and it was based on four ferroptosis-related genes. This model predicted the prognosis of patients with liver cancer; 43 Studies have also been conducted to understand the correlation between ferroptosis and breast cancer patients, head and neck squamous cell carcinoma, and renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…What is more, LINC00662 is also closely related to gastric cancer, glioma, chordoma, and so on ( Liu et al, 2018a ; Wu et al, 2020b ; Wang et al, 2020 ). The remaining lncRNAs in the 8-lncRNA signature were associated with lung adenocarcinoma, colon cancer, and so on ( Liu et al, 2018b ; Cai et al, 2021 ). The research directed at the lncRNA in the multi-lncRNA signatures of ESCC and EAC was still deficient.…”
Section: Discussionmentioning
confidence: 99%